A feasibility cluster randomised controlled trial of a paramedic-administered breathlessness management intervention for acute-on-chronic breathlessness (BREATHE) - Matthew Northgraves; Judith Cohen; Victoria Allgar; David Currow; Simon Hart; Kelly Hird; Andrew Hodge; Miriam Johnson; Suzanne Mason; Flavia Swan; Ann Hutchinson (ERJ Open Research, 2021)
Chronic breathlessness, persistent and disabling despite optimal treatment of underlying causes, is a prevalent and frightening symptom and is associated with many emergency presentations and admission to hospital. Breathlessness management techniques used by paramedics may reduce the need for conveyance to hospital. The Breathlessness RElief AT HomE study (BREATHE) aims to explore the feasibility of conducting a definitive cluster randomised controlled trial (cRCT) for people with acute-on-chronic breathlessness who have called an ambulance, to evaluate the effectiveness and cost-effectiveness of a paramedic-administered non-pharmacological breathlessness intervention. The trial is a mixed-methods feasibility cRCT. Eight paramedics will be randomised 1:1 to deliver either the BREATHE intervention in addition to usual care or usual care alone at call-outs for acute-on-chronic breathlessness. Sixty participants will be recruited to provide access to routine data relating to the index call-out with optional follow-up questionnaires at 14 days, 1 month and 6 months. An in-depth interview will be conducted with a subgroup. Feasibility outcomes relating to recruitment, data quality (especially candidate primary outcomes), and intervention acceptability and fidelity will be collected as well as providing data to estimate a sample size for a definitive trial. Yorkshire and The Humber–Sheffield Research Ethics Committee approved the trial protocol (19/YH/0314). The study results will inform progression to, or not, and design of a main trial according to predetermined stop-go criteria. Findings will be disseminated to relevant stakeholders and submitted for publication in a peer-reviewed journal.